Some observations on leucocytozoon caulleryi infections in chickens - Whitten, L. K.; Allison, F. R.; Oh, Beng Tatt (1982)

(untitled)
A group of 48 birds were observed and blood samples were examined every week for 8 weeks. The birds were kept in raised open-mesh cages and were fed a ration with no prophylactic. Twenty-two birds became infected and two of them died of the disease. Four birds died of other causes. Infected birds showed positive blood smears for only one or two weekly bleedings and were clear thereafter. There were no cases in a similar group fed with 30 ppm sulphamonomethoxine and bled on one occasion.